Paradigm Reconstruction of the Protected Legal Interests in China’s Crime of Money Laundering - Yaoying Huang (Studies in Law and Justice, 2025)
Since the Criminal Law Amendment (XI) established the punishability of self-laundering, the systemic dilemmas faced by traditional legal interest theories in interpreting the constitutive elements of the Crime of Money Laundering have become increasingly evident. The understanding of the legal interests protected by the Crime of Money Laundering serves as the foundation for interpreting its constitutive elements and the guiding principle for its judicial application. Through a critical analysis of the deficiencies in existing doctrines, this paper proposes a dual-structure theory of protected legal interests: “result-oriented financial management order” and “control rights over proceeds derived from predicate offenses.” The former, grounded in the consequence of regulatory failure, emphasizes transcending the traditional paradigm that narrowly equates Money Laundering with the instrumentalization of financial tools. The latter, by synthesizing the rational core of the “judicial function theory” and the “protected legal interests theory of predicate crimes,” reconstructs the independent legal interest boundaries distinguishing Money Laundering from traditional crimes involving proceeds of crime. This theoretical framework not only rationally explains the regulatory logic of judicial interpretations governing non-financialized laundering behaviors but also provides substantive criteria for differentiating Money Laundering from crimes involving proceeds of crime. It holds methodological significance for refining China’s criminal governance system against money laundering.